Antimicrobial Resistance and Molecular Epidemiological Characteristics of Methicillin-Resistant and Susceptible Staphylococcal Isolates from Oral Cavity of Dental Patients and Staff in Northern Japan - Mina Hirose; Meiji Soe Aung; Atsushi Fukuda; Shoko Yahata; Yusuke Fujita; Masato Saitoh; Yukito Hirose; Noriko Urushibara; Nobumichi Kobayashi (MDPI AG, 2021)
The acquisition of drug resistance and virulence by staphylococcal species colonizing humans is a growing public health concern. The present study was conducted to investigate the prevalence, antimicrobial resistance and genetic characteristics of Staphylococcus isolates from the oral cavity and skin (hand) of systemically healthy subjects with dental disease and dental staff in northern Japan. Among a total of 133 subjects (91 patients and 42 staff), 87 coagulase-positive Staphylococcus (83 S. aureus/4 S. argenteus) and 162 coagulase-negative Staphylococcus (CoNS) isolates were recovered from 59 (44.4%) and 95 (71.4%) subjects, respectively. Three oral isolates were methicillin-resistant S. aureus (MRSA) (3.6%, 3/83) that were genotyped as ST8-SCCmec-IVl, ST4775(CC1)-SCCmec-IVa and ST6562(CC8)-SCCmec-IVa. Remarkably, the ST6562 isolate harbored PVL genes on ΦSa2usa and type I ACME (arginine catabolic mobile element). Four methicillin-susceptible isolates were identified as S. argenteus belonging to ST1223 and ST2250, which harbored enterotoxin genes egc-2 and sey, respectively. Among the fourteen CoNS species identified, methicillin-resistant (MR) isolates were detected in five species (11 isolates, 13.3% of CoNS), with S. saprophyticus and S. haemolyticus being the most common. ACME was prevalent in only S. epidermidis and S. capitis. These findings indicated the potential distribution of USA300 clone-like MRSA, toxigenic S. argenteus and MR-CoNS in the oral cavity of dental patients.